Hubungan kualitas informasi website RS Paru Dr. H. A. Rotinsulu dengan pemenuhan kebutuhan informasi - Hafizhah Nur Aghnia; Neneng Komariah; Edwin Rizal (Jurnal Kajian Informasi dan Perpustakaan, 2019)
The official website of an institution on the quality of information about the institution's profile and the services offered at the institution can help for people who need information about hospital services. This study aimed to determine the relationship between the quality of information on the official website of Dr. H.A. Rotinsulu Hospital and meeting the information needs of visitors. This study used a quantitative correlational method with a study population of visitors to Dr. HA Rotinsulu, Lung Hospital website, who conducted online consultations, with a sample of 50 respondents was obtained. Research data were collected using questionnaires, interviews, and literature studies. The inferential correlation test used a simple linear regression analysis test using the product moment formula. The results showed a significant relationship between the quality of information, both from indicators of accuracy, timeliness, and relevance of information, with the fulfillment of cognitive needs and personal integrity of website visitors. This was proven by testing the mayor hypothesis, and the calculation results obtained a correlation coefficient of 0.738 with a coefficient of determination of 0.544. Furthermore, it got a tcount of 8,253 and a ttable of 1,677. Thus, the tcount was higher than the ttable, so the hypothesis was accepted. This means that website visitors considered that the information presented had high accuracy, high punctuality, and high relevance to meet cognitive needs and personal integrity. Then, the information presented on Dr. H.A. Rotinsulu Hospital website is of high quality and can meet the information needs of its visitors.